Sustainable synthesis of α-ketoglutaric and methanetriacetic acids from biomass feedstocks - Cheng-Bin Hong; Wangde Hua; Lieke Liu; Haichao Liu (Nature Communications)
Abstract α-Ketoglutaric acid (KGA) and methanetriacetic acid (MTA) are important multi-functional carboxylic acids with versatile applications. However, their synthetic processes are still not green and efficient. Herein, we report a novel one-pot approach for sustainable synthesis of KGA and MTA from biomass-derived pyruvic and glyoxylic acids under mild conditions. KGA is synthesized via cross-aldol condensation of pyruvic and glyoxylic acids to 2-hydroxy-4-oxopentanedioic acid, followed by its sequential dehydration and hydrogenation on Pd/TiO2, affording a high yield of 85.4% on a molar basis of glyoxylic acid at 110 °C and 1.0 MPa H2. The synthesis of MTA involves cross-aldol condensation of KGA and glyoxylic acid to 3-(carboxymethyl)-2-hydroxy-4-oxopentanedioic acid and its subsequent hydrodeoxygenation on Pd/TiO2 and MoOx/TiO2 in a high yield of 86.2% at 200 °C and 2.0 MPa H2. This novel approach provides a rationale for the sustainable production of various multi-functional carboxylic acids that are still not easily available.